Recent Findings on the Role of Gelatinases (Matrix Metalloproteinase-2 and -9) in Osteoarthritis - Olimpio Galasso; Filippo Familiari; Marco De Gori; Giorgio Gasparini (Advances in Orthopedics)
Several studies dealing with the pathomechanisms of OA refer to MMP-1, -3, -7, -8, and -13 whereas a smaller number of investigations have pointed out the pathogenic role of gelatinases in OA. These gelatinases are best known for their involvement in pulmonary, myocardial, and neoplastic disease but they are emerging as important proteases implicated in the OA progression. This paper highlights the role of the gelatinases as emerging factors in OA pathogenesis through the regulation of subchondral bone resorption and microvascular invasion. The most significant new findings over the last year that add to our knowledge of the activity of these proteins in OA have been reported.